Human tooth germ stem cell response to calcium-silicate based endodontic cements (Journal of Applied Oral Science, 2013)
OBJECTIVE: The aim of this study was to compare the cytotoxic effects of endodontic cements on human tooth germ stem cells (hTGSCs). MTA Fillapex, a mineral trioxide aggregate (MTA)-based, salicylate resin containing root canal sealer, was compared with iRoot SP, a bioceramic sealer, and AH Plus Jet, an epoxy resin-based root canal sealer. MATERIAL AND METHODS: To evaluate cytotoxicity, all materials were packed into Teflon rings (4 mmµ3 mm) and co-cultured with hTGSCs with the aid of 24-well Transwell permeable supports, which had a pore size of 0.4 µm. Coverslips were coated with MTA Fillapex, iRoot SP and AH Plus Jet and each coverslip was placed onto the bottom of one well of a six-well plate for scanning electron microscopy (SEM) analysis. Before the cytotoxicity and SEM analysis, all samples were stored at 37ºC and at 95% humidity and 5% CO2 for 24 hours to set. The cellular viability was analyzed using MTS test (3-(4,5-dimethyl-thiazol-2-yl)-5-(3-carboxy-methoxy-phenyl)-2-(4-sulfo-phenyl)-2H-tetrazolium). The cytotoxic effects and SEM visualization of the tested materials were analyzed at 24-hour, 72-hour, one-week and two-week periods. RESULTS: On the 1st day, only MTA Fillapex caused cytotoxicity compared to negative control (NC) group (p;0.05). After 14 days of incubation with the test materials, MTA Fillapex exhibited significantly higher cytotoxicity compared with iRoot SP, AH Plus Jet and the NC group (P